Effect of copaiba oil on correction of abdominal wall defect treated with the use of polypropylene/polyglecaprone mesh - Yasojima,Edson Yuzur (2013)
PURPOSE: To evaluate the effects of copaiba oil on the correction of abdominal defect treated with the use of polypropylene/polyglecaprone mesh in rats. METHODS: A defect in the abdominal wall was created and corrected with polypropylene/polyglecaprone mesh in 36 rats. They were randomly distributed into three groups: control, copaiba by oral administration (gavage) and copaiba oil dip in the mesh. Euthanasia was performed after seven, 14 and 21 post-operative days. The healing process was analyzed regarding the meshes and macroscopic and microscopic aspects. RESULTS: All animals had abdominal adhesions, which were smaller in the copaiba (gavage) group (p<0.05). In microscopy, all animals had an acute inflammation stage and the inflammatory response was best characterized by foreign body-type granulomas around the mesh fragments, which was not found in the mesh fragments within the copaiba dip group. There was a greater area of necrosis and fibrosis in the copaiba dip group compared to the control group (p<0.05). The copaiba (gavage) group had a greater quantity of collagen fibers compared to the control group. CONCLUSION: Copaiba oil administered by gavage decreased the amount of abdominal adhesions, besides accelerating the process of collagen fibers formation, without damages within the early stages of healing. However, when used by dip directly on the mesh, it had corrosive effects compromising the healing process of the abdominal wall.